Why Meadow died : the people and policies that created the Parkland shooter and endanger America's students - Pollack, Andrew, 1966-; Eden, Max (Post Hill Press, 2019)
Andrew Pollack, whose daughter Meadow was murdered in the Parkland, Florida high school shooting, teamed up with education expert Max Eden to find out how the Parkland shooter slipped through the cracks. They argue that the policies pioneered in Broward plague American schools, and make school shootings more likely.